Large‐Scale Synthesis of Isotropic Single‐Crystalline ScF3 Cubes by Hydrothermal Method. Issue 5 (1st April 2014) - Hu, Lei; Chen, Jun; Pan, Zhao; Deng, Jinxia; Yu, Ranbo; Xing, Xianran; Barnes, P.
<x xml:space="preserve">Abstract</x> Scandium fluoride (ScF3) belongs to one of the rare compounds which exhibit isotropic negative thermal expansion. Here, a facile and environmentally friendly hydrothermal synthesis method has been presented. High‐quality single‐crystalline ScF3 cubes, with an average size of 200 nm, can be easily fabricated in a large scale. Sc(NO3)3 and NH4HF2 were used as precursors. The as‐prepared ScF3 demonstrates cubic symmetry (Pm‐3 m), which was confirmed by X‐ray diffraction and selected‐area electron diffraction. Its uniform morphology and size were characterized by high‐resolution transmission electron microscopy. Furthermore, thermal analysis was also performed in argon gas atmosphere to investigate its thermal stability.